Papillon - Charriere, Henri, 1906-1973 (HarperCollins, 1994)
The first UK edition (a different translation was published in the US the same year). 8vo. 566pp. Brown boards lettered in gold at spine. Map-illustrated endpapers. A touch of wear to the spine ends. A nice crisp copy in non-price-clipped dust wrapper, lightly creased in places and with the publisher's laminate lifting a fraction in one or two areas. Former owner name inked to the head of the half-title. Charrière's autobiographical account of his fourteen-year incarceration and eventual escape from a penal colony in French Guiana, memorably filmed three years later with Steve McQueen and Dustin Hoffman [damn, that McQueen could conceal a shank!]